Analisis Motivasi Kerja Pegawai pada Bagian Kesejateraan Rakyat (KESRA) SETDA Kota Bima - Yuyun Nailufar; Firmansyah Kusumayadi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This research aims to find out how high or low work motivation is in employees of the People's Welfare Section (KESRA) of Bima City SETDA. The research sample was 33 employees. Data collection techniques using observation, questionnaires and literature study. The data analysis technique uses a one sample t test. The results of the research show that the t-calculated value for the Motivation variable = 70.506 > 1.693 with a significance level of 0.000 < 0.05. Thus Ha was accepted which stated the work motivation of employees in the People's Welfare (Kesra) Section of the Regional Secretariat of Bima Tinggi City.